The collagen I mimetic peptide DGEA enhances an osteogenic phenotype in mesenchymal stem cells when presented from cell‐encapsulating hydrogels. Issue 11 (24th May 2015) - Mehta, Manav; Madl, Christopher M.; Lee, Shimwoo; Duda, Georg N.; Mooney, David J.
Abstract Interactions between cells and the extracellular matrix (ECM) are known to play critical roles in regulating cell phenotype. The identity of ECM ligands presented to mesenchymal stem cells (MSCs) has previously been shown to direct the cell fate commitment of these cells. To enhance osteogenic differentiation of MSCs, alginate hydrogels were prepared that present the DGEA ligand derived from collagen I. When presented from hydrogel surfaces in 2D, the DGEA ligand did not facilitate cell adhesion, while hydrogels presenting the RGD ligand derived from fibronectin did encourage cell adhesion and spreading. However, the osteogenic differentiation of MSCs encapsulated within alginate hydrogels presenting the DGEA ligand was enhanced when compared with unmodified alginate hydrogels and hydrogels presenting the RGD ligand. MSCs cultured in DGEA‐presenting gels exhibited increased levels of osteocalcin production and mineral deposition. These data suggest that the presentation of the collagen I‐derived DGEA ligand is a feasible approach for selectively inducing an osteogenic phenotype in encapsulated MSCs. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3516–3525, 2015.